CHALLENGES AND STRATEGIES IN ISLAMIC RELIGIOUS EDUCATION IN THE FACE OF DIGITAL DISRUPTION - Nilda Nilda (Adisam Publisher, 2025)
Digital disruption has fundamentally changed the landscape of education. Islamic Religious Education (IRE), as a subject that focuses on character building and spiritual morality, faces a double challenge: adapting to technology while preserving Islamic values amid the rapid flow of information. This study aims to analyse in depth the main challenges faced by PAI learning in the era of digital disruption and formulate effective innovative strategies. The challenges identified include the digital competency gap among teachers, the polarisation of religious understanding (radicalism and liberalism) facilitated by digital platforms, and the issue of data privacy ethics in learning. The proposed strategies include the development of a PAI curriculum based on digital literacy and artificial intelligence (AI) ethics, enhancing teacher professionalism through interactive digital pedagogy training, and implementing a blended-synchronous learning model that integrates direct spiritual experiences with digital simulations. This research uses a qualitative-descriptive approach based on literature studies and educational policy analysis. The results show that the success of PAI in the digital era is highly dependent on the cultural transformation of educational institutions, not merely the adoption of hardware.